Analysis of Public Transport Network Services on Area Development in Doloksanggul District Humbang Hasundutan Regency - Hutapea, Timbul Parningotan; Sirojuzilam, Sirojuzilam; Purwoko, Agus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Transportation plays a big role in the development of an area. The movement of people, goods and services from one place to another can be facilitated by good transportation. Transportation has a significant relationship to regional development. Currently, public transportation services in Humbang Hasundutan Regency, especially Doloksanggul is considered still less than optimal due to the fact that the existing public transportation is not on a fixed and regular route, causing uncertainty in waiting for public transportation. The objectives of this study are to: 1) Analyze the effect of the number of fleets, passenger capacity and route routes on the accessibility of the community in the District. Doloksanggul, 2) Analyzing the effect of the number of fleets, passenger capacity and route routes on road connectivity in Doloksanggul District, and 3) Analyzing the effect of community accessibility and road connectivity on regional development in Doloksanggul District. The research was conducted in Doloksanggul District, Humbang Hasundutan Regency. The analytical method used in this research is multiple regression analysis with the number of respondents as many as 100 people. The results showed that the number of fleets, passenger capacity and route routes had a positive and significant effect on community accessibility in Doloksanggul District, the number of fleets, passenger capacity and route routes had a positive and significant effect on road connectivity in Doloksanggul District, community accessibility and Road connectivity has a positive and significant effect on regional development in Doloksanggul District.